Socio-economic impact of heart failure in Russia - O. M. Drapkina; S. A. Boytsov; V. V. Omelyanovskiy; A. V. Kontsevaya; M. M. Loukianov; V. I. Ignatieva; E. V. Derkach (Российский кардиологический журнал, 2021)
Heart failure (HF) significantly worsens the patient quality of life and leads to the disability of their significant part, as well as increases the risk of death, which in turn causes economic damage.Aim. To assess the annual socio-economic impact of HF in Russia.Material and methods. To assess the socio-economic impact of HF, a model was developed, which assessed the number of HF patients seeking medical care (data from the epidemiological studies), the number of those with disabilities and the mortality rate among them. We also evaluated the costs of drug therapy (data from the government procurement reports) and hospitalization (data from the compulsory health insurance tariffs), social benefits due to disability, and death impact on the gross domestic product. Data on the prescription rate, hospitalizations and mortality was obtained from Russian registries of patients with cardiovascular diseases. Using the foreign study, the costs of family caregiving were also calculated.Results. According to modeling data, there are 7,1 million people with HF seeking medical care in Russia. In this case, the annual economic impact of HF in the context of government spending, is RUB 81,86 billion, including medical costs of RUB 18,6 billion, direct nonmedical costs of RUB 47,1 billion, and indirect costs of RUB 16,2 billion. The impact of family caregiving is RUB 72,4 billion. In the structure of medical expenses, 73,6% is hospitalization costs, while the main costs of drug therapy are borne by patients, since only a part of them (19,6%) receive the necessary medications within assistance programs. In patients with HF with reduced ejection fraction, medical costs are 56% higher than in patients with HF with preserved ejection fraction.Conclusion. HF causes significant economic burden to the state. Improving the healthcare system for this category of patients, including preferential drug provision, will reduce HF-related mortality, the healthcare system costs and, accordingly, reduce the economic impact on the state and society.